PEMBUATAN WEBSITE PENJUALAN KAIN DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN PHP: Studi Kasus : CV. Grhtexindo Textile - Muhammad Naufal Rizqi Hartanto; Novita Anggraini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
One company that has begun to transition to digital is an online store as a result of the increasingly sophisticated technological development. For traders and consumers who conduct business online, an online store serves as a hub. a CV firm. A factory called GRHTEXINDO only makes fabrics when a customer places an order, so they never go on backorder. As a result of the company's perception that there are still issues with offline sales, the company now intends to develop fabrics and sell them online. The author is motivated to create a website that can assist businesses in implementing the waterfall approach to sell their items online after realizing the aforementioned issues. The PHP programming language was used to create this website because it is well-known for creating websites and is simple to grasp. As a result, practically all Indonesians can already easily visit the website via PC, laptop, and smartphone. It is believed that the outcomes of this website will assist businesses with initiating product sales and sales reports.